4CPS-196 Patients receiving clozapine: closing the gap between community and hospital pharmacists. (23rd March 2022) - Hurley, K; Halleran, C; Foley, E; Cunningham, J; O'Brien, S; Sahm, L; Hoctor, F
Abstract : Background and importance: In Ireland, the antipsychotic clozapine can only be dispensed from hospital pharmacies. This means that patients receive their clozapine from a hospital pharmacy but receive other medications from their community pharmacy. Studies have shown that continuity of care for this patient cohort is suboptimal as community pharmacists are largely unaware that their patients are receiving clozapine. Other literature demonstrates that this can result in a high incidence of drug–drug interactions (DDIs) and increased prevalence of metabolic syndrome (MetS) relative to those who do not receive clozapine. Aim and objectives: The aim of this study was to examine the continuity of care for patients who are prescribed clozapine. Material and methods: This study was conducted in the Mercy University Hospital (MUH) Pharmacy Department and the Clozapine Clinic in Cork North Lee Mental Health Services. A retrospective audit of those receiving clozapine assessed demographic information, comorbidities, physical health characteristics, comedications, and side effect profile. DDIs between clozapine and coprescribed medicines was assessed using Lexicomp and Stockley's Interaction Checker (SIC). Prevalence of MetS was determined using the International Diabetes Federation (IDF) criteria. Patients were eligible for inclusion if aged 18 years or more, registered with the clozapine patient monitoring service, and had the capacity for informed consent. Microsoft Excel and R were used for data collation and analysis. Results: Of the 148 eligible patients, three patients did not agree to participate, leaving 145 patients (32% female, median age 43.8 years) who provided written informed consent. Of these, 116 of patients were prescribed a total of 615 medicines in addition to clozapine. By using Lexicomp it was found that 58.3% had DDIs with clozapine, while SIC found 54.3%. In 32 of these cases, advice stated that the combination should be avoided or contraindicated. The prevalence of MetS was 61.4% (n=86) and univariate results in subjects with and without MetS showed statistically significant differences in waist circumference, current weight, systolic and diastolic blood pressure, triglycerides, high-density lipoprotein-cholesterol (HDL-C), fasting plasma glucose and glycated haemoglobin (HbA1c). Conclusion and relevance: This study demonstrates the need for improved communication between primary and secondary care. Healthcare professionals should closely monitor physical health and side effect burdens regularly and consider treating metabolic abnormalities in this patient group. References and/or acknowledgements: Conflict of interest: No conflict of interest